Digital governance and public service accountability: Insight from the population and civil registration office in Makassar, Indonesia - Nasrullah, Nasrullah; Rijal, Rijal; Jusman, Jusman (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
This research aims to explore the relationship between the applicability of digital governance in improving public service accountability and how data integration is implemented in the application of digital technology at the population and civil registration office of Makassar City. The highlighted issue is how service digitization contributes to transparency, efficiency and integrated public accountability. The research used an explanatory qualitative approach; which consisted of data collection techniques through in-depth interviews, review and analysis of official documents on digital-based service reports and direct observation of digital service platforms. Data analysis was conducted interactively through the stages of data reduction, data presentation, verification and and conclusion. The findings showed that digital governance at the population and civil registration office of Makassar City has improved to adapt to digital technology, thereby increasing effectiveness and public access to services. However, several improvement notes need to be improved, such as; aspects of data sustainability and security still require strengthening at the institutional level, increasing the capacity of human resources, and policy integration between local and national levels. Through comparisons with local research and with best practices at the global level, this research has reconstructed some concepts of e-government and good governance, while highlighting the need for appropriate adaptation to the local context. The contribution of this research consists in identifying and mapping the practical and normative challenges in implementing digital transformation in the public service sector at the local level.